2018
DOI: 10.1177/0956797618799302
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Attentional Engagement: Stimulus- and Goal-Driven Capture Have Qualitatively Different Consequences

Abstract: We examined whether shifting attention to a location necessarily entails extracting the features at that location, a process referred to as "attentional engagement". In three spatial-cueing experiments (N=60) we found an onset cue to capture attention both when it shared the target's color and when it did not. Yet, the effects of the match between the response associated with the cued object's identity and the responses associated with the target (compatibility effects), which are diagnostic of attentional eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
(57 reference statements)
1
35
0
Order By: Relevance
“…Our findings raise the possibility that in some of these studies, attention was in fact captured by distractors that did not share the target feature, but was not engaged. Consistent with this conjecture, recent studies show that abrupt onsets outside the attentional set can capture attention (Folk & Remington, 2015;Gaspelin, Ruthruff & Lien, 2016), but do not result in attentional engagement (Zivony & Lamy, 2018). Additional research is required to further distinguish between the boundary conditions of attentional engagement and attentional capture.…”
Section: Implications For the Attentional Capture Literaturementioning
confidence: 86%
See 1 more Smart Citation
“…Our findings raise the possibility that in some of these studies, attention was in fact captured by distractors that did not share the target feature, but was not engaged. Consistent with this conjecture, recent studies show that abrupt onsets outside the attentional set can capture attention (Folk & Remington, 2015;Gaspelin, Ruthruff & Lien, 2016), but do not result in attentional engagement (Zivony & Lamy, 2018). Additional research is required to further distinguish between the boundary conditions of attentional engagement and attentional capture.…”
Section: Implications For the Attentional Capture Literaturementioning
confidence: 86%
“…In contrast, attentional engagement allows the transfer of the extracted information to higher-level processing, which requires recurrent activation of neural networks (Töllner et al, 2012). Moreover, the conditions necessary for attentional engagement are more restrictive than the conditions necessary for attentional shifting (Zivony & Lamy, 2018), possibly due to the high cost incurred by engaging attention to an irrelevant object.…”
Section: The N2pc As An Index Of Attentional Engagement Onsetmentioning
confidence: 99%
“…More recent studies have shown that stimulus-driven and goals-driven factors might contribute differently to these two mechanisms. For instance, Zivony and Lamy [90] presented supraliminal abrupt-onset cues followed by a display of four letters. The task was to find the red-lettered target (e.g., “E”) among distractors (“E” and “H” in pink/orange) and press a button accordingly.…”
Section: Possible Explanations For the Inconsistenciesmentioning
confidence: 99%
“…Most of the studies using the spatial cuing paradigm with unconscious cues have measured cuing effects, and thus only the extent of attention capture but not attentional engagement is known. The crucial distinction made by Zivony and Lamy [90] is that shifts of spatial attention during capture are “shallow” and can occur irrespective of top-down goals. However, further enhanced processing of the identity of the object at the cued location is costly and occurs only if it is necessary for the task at hand.…”
Section: Possible Explanations For the Inconsistenciesmentioning
confidence: 99%
See 1 more Smart Citation